(3GdYLH GdYLGH ajeG jQi aj GdOgQ ef GdGfbdGHs - (3YeQ Hf YHO GdbGOQ Hf MSf Hf jhSa GdMeUj, GdHcQjs
(3ChdgG (B:s
(3CeG HYO aEf GdOGYi Edi fSN gPG GdcJGH CehQ ZQGH hGMhGd UYGH Ef eDda gPG GdcJGH GdeHGQc CQGO Cf jKjQ Edi eG LQi dg ef Chd YeQg ai GdOfjG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B212 s
(3eUOQ GbJfGA GdCUd (B:s
(3JhHfLf (B(26) s
Keywords: (3GdJGQjNs